COVID-19 Sepsis and Microcirculation Dysfunction - Colantuoni, Antonio; Martini, Romeo; Caprari, Patrizia; Ballestri, Marco; Capecchi, Pier Leopoldo; Gnasso, Agostino; Lo Presti, Rosalia; Marcoccia, Antonella; Rossi, Marco; Caimi, Gregorio (Frontiers in Physiology, 2020)
The spreading of Coronavirus (SARS-CoV-2) pandemic, known as COVID-19, has caused a great number of fatalities all around the World. Up to date (2020 May 6) in Italy we had more than 28,000 deaths, while there were more than 205.000 infected. The majority of patients affected by COVID-19 complained only slight symptoms: fatigue, myalgia or cough, but more than 15% of chinese patients progressed into severe complications, with acute respiratory distress syndrome (ARDS), needing intensive treatment. We tried to summarize data reported in the last months from several Countries, highlighting that COVID-19 was characterized by cytokine storm (CS) and endothelial dysfunction in severely ill patients, where the progression of the disease was fast and fatal. Endothelial dysfunction was the fundamental mechanism triggering a pro-coagulant state, finally evolving into intravascular disseminated coagulation, causing embolization of several organs and consequent multiorgan failure (MOF). The Italian Society of Clinical Hemorheology and Microcirculation was aimed to highlight the role of microcirculatory dysfunction in the pathogenetic mechanisms of COVID-19 during the spreading of the biggest challenges to the World Health.